Improving the quality of hospital discharge summaries utilising an electronic prompting system. Issue 1 (26th August 2014) - Maurice, Andrew P; Chan, Samuel; W Pollard, Clifford; Richard A Kidd; J Ayre, Stephen; E Ward, Helen; L Walters, Darren
Abstract: The discharge summary (DS) is a summary of an inpatient admission, patient's health state, and future treatment plans which is delivered to the patient's primary care provider. The DS is often incomplete, inaccurate, or unclear. The aim of this project was to improve the quality of the DS through the use of an electronic prompting system. The electronic prompting system was implemented in the acute medical and surgical wards of the hospital as an adjunct to a pre-existing, widely used hospital program that documents all the patients in a ward or belonging to a particular treating team. When using the program, a doctor enters information (with the assistance of the treating consultant) from a drop-down menu and is prompted to include common, departmental specific diagnoses, co-morbidities, complications, and procedures that were commonly missed or documented incorrectly in the DS. Fifteen DSs were randomly selected from a two month period immediately prior to the intervention period and were rated by an external, experienced general practitioner (GP) using a scoring system consistent with the Australian Medical Association Guidelines for quality DSs. Fifteen random DSs from a two month period, four months post-implementation were also rated by the same GP. The quality of the DS improved in all categories evaluated. The overall quality improved from mean (± SD) 2.86 ± 1.64 to 4.13 ± 0.92 out of 5 (p = 0.031). Additionally the implementation of the system was associated with improvements in documentation of the diagnosis, co-morbidities and other relevant clinical information. In summary, electronic prompting systems can improve the quality of DSs to ensure the information contained within the DS is more accurate and complete.